2020
DOI: 10.1088/1742-6596/1497/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

The effective connectivity of the default mode network following moderate traumatic brain injury

Abstract: The effective connectivity can reveal the causal relationships between nodes of the Default Mode Network (DMN), which may reveal any impairment to the network following moderate traumatic brain injury (MTBI). Eight sub-acute MTBI patients and eight controls were recruited for this study. The results indicated that effective connectivity (EC) within MTBI group was higher in number and strength compared to the controls. Moreover, the network hubs within DMN are associated with increased connection strength in MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Moreover, the TBI group displayed more inhibitory connectivity compared to HC. This finding is in line with our previous study, which found more negative ECs in the TBI group with higher strength ( Abdul Rahman et al, 2020 ). The extrinsic inhibitory connections are the negative influence exerted by one region to another, also known as the baseline inhibition ( Stephan and Friston, 2010 ), due to the population of inhibitory neurons.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, the TBI group displayed more inhibitory connectivity compared to HC. This finding is in line with our previous study, which found more negative ECs in the TBI group with higher strength ( Abdul Rahman et al, 2020 ). The extrinsic inhibitory connections are the negative influence exerted by one region to another, also known as the baseline inhibition ( Stephan and Friston, 2010 ), due to the population of inhibitory neurons.…”
Section: Discussionsupporting
confidence: 94%